2013
DOI: 10.4103/0300-1652.126292
|View full text |Cite
|
Sign up to set email alerts
|

Trends of tuberculosis prevalence and treatment outcome in an under-resourced setting: The case of Enugu state, South East Nigeria

Abstract: Background:The burden of tuberculosis (TB) in Nigeria is high. Unfortunately, the data from the TB programme of the States’ ministries of health are usually unpublished, which possibly contribute to the prevailing ignorance and poor attitude of Nigerians to the disease. This study determined the trends of TB burden and treatment outcome in Enugu state, Nigeria; and relate the State's disease burden to that of the Nation.Materials and Methods:A descriptive study of secondary data from the TB control programme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 8 publications
7
31
2
Order By: Relevance
“…Default rates, death rates, and failure rates of 9.8%, 6.5%, and 1.5% respectively were still within the national range [18]. It was also similar to what was obtained in Enugu state, Nigeria [49] and in a study from India [26]. This high default rate is of great concern due to its public health implication in spreading the disease and in the emergence of resistance strains of the TB organism.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Default rates, death rates, and failure rates of 9.8%, 6.5%, and 1.5% respectively were still within the national range [18]. It was also similar to what was obtained in Enugu state, Nigeria [49] and in a study from India [26]. This high default rate is of great concern due to its public health implication in spreading the disease and in the emergence of resistance strains of the TB organism.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, the treatment success found in this study was higher than figures reported in studies from, Nnewi, (61.3%) [19] Owo Ondo state, (75.5%) [51] Ibadan (76.6%) [17], Ebonyi state, (65.8%) [40], Abuja, (65.8%) [39] all from Nigeria and in Limpopo South Africa, (74.4%) [25]. Yet our findings compares favorably with the treatment successes reported in some other studies; 82% from a study in Enugu state [49], 80% in another study from Ebonyi state [56], 83.4% in India [26] and 82.7% in Addis Ababa, Ethiopia [23]. This variations in treatment success is likely to have been caused by various socio-demographic/economic factors, issues related to drug compliance and monitoring, nutritional status of individuals, the HIV pandemic, and drug susceptibility/resistance among others which varies greatly from place to place.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The African Region had approximately one quarter of the world's cases, and the highest rates of cases and deaths relative to population, while India and China had the largest number of cases, 24% and 11% of the global total respectively [2]. Although the 2015 millennium development goal of halting and reversing the TB incidence has been achieved globally, in all six WHO regions and in most of the 22 high TB burden countries, and TB incidence fell at an average rate of about 1.5% per year between 2000 and 2013 [2], the burden of TB in Nigeria remains high [4]. Also, the burden of both TB and HIV infections in Nasarawa State, Nigeria is also relatively high while TB diagnostics are grossly inadequate [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent descriptive study of secondary data from a TB control programme showed that the annual number of all TB cases increased from 914 cases in the year 2000 to 1684 in 2009; and that while the proportion of new sputum smear diagnoses of pulmonary TB declined, extra-pulmonary TB cases increased by about four fold. 31 This is evidence that pulmonary TB as a clinical condition is being managed and monitored by the practitioners in the country. There is also a report that the Federal Ministry of Health has established ten reference laboratories and scaled up GeneXpert technology from 9 in 2011 to 52 in 2013 to enhance diagnosis of drug susceptible and drug resistant TB.…”
Section: Update From Literature -Brief Narrativementioning
confidence: 99%